Pembuatan Prototype Pengereman Turbin Pada Pembangkit Listrik Tenaga Bayu Dengan Menggunakan Dummy Load Resistor - Agil Herlambang Rizki; Irrine Budi Sulistiawati; Bima Romadhon Romadhon PDP (Universitas Darul Ulum, 2024)
This study aims to develop a prototype braking system for wind turbines used in wind power plants by utilizing a dummy load resistor. The background of this research is the necessity for an effective braking system to control the speed of wind turbines, especially under extreme wind conditions, which can cause damage to the system and electrical components. The designed braking system uses a dummy load resistor to reduce the rotational speed of the turbine by dissipating excess electrical energy as heat. Tests were conducted to evaluate the effectiveness of the system under various wind conditions and to measure performance parameters such as turbine speed stability and protection of electrical components. The results show that the uses of dummy load resistors are effective in diverting excess voltage with a set point of 14 volts, and at 300 rpm using voltage sensors, proximity sensor and MOSFETs as voltage control, which will be diverted to the dummy load resistor system. Thus, this research makes a significant contribution to the development of wind power technology, particularly in terms of safety and operational efficiency.